Usefulness of estimation of cord blood lipopolysaccharide binding protein and neutrophilic elastase concentration versus C-reactive protein concentration in the prediction of early-onset neonatal infections - Kordek, Agnieszka; Błażejczak, Anna; Kordek, Justyna (Journal of Education, Health and Sport, 2025)
Introduction. Congenital infection in a newborn is an infection caused by pathogens passed on to the child by the mother intrauterine or perinatally. Sepsis is the most common form of early-onset infection in newborns. The diagnosis in the newborn is difficult due to the absence of characteristic clinical signs as well as specific and infection-specific laboratory deviations. Objective. The study was conducted to estimate the predictive value of cord blood plasma concentration of lipopolysaccharide-binding protein, and neutrophil elastase in the prediction of early onset sepsis in preterm and full-term neonates. Correlation with C-reactive protein was assessed. Materials and methods. Patients enrolled in the study (n=153) were divided in 4 groups: B-I- 39 infected preterm; B-II- 24 infected full-term; K-I- 45 non-infected preterm and K-II- 45 full-term neonates without signs of infection. The research material was umbilical cord taken immediately after delivery in the presence of risk factors for infection and without risk factors for obtaining a control group. The concentration of lipopolysaccharide binding protein, activity of neutrophilic elastase and CRP concentration were determined in the collected samples. Results. The cord blood plasma LBP and neutrophil elastase concentration was higher in infected preterm and term neonates. Cord blood LBP is a highly specific and sensitive biomarker of sepsis immediately after birth. High levels of LBP and neutrophil elastase in cord blood correlate with CRP. Conclusions. Measuring the concentration of LBP and neutrophil elastase in cord blood plasma may help in the detection of early onset sepsis in newborns with prenatal risk factors.